ANALISIS KEMAMPUAN KERJA KARYAWAN BERDASARKAN FAKTOR PENGALAMAN KERJA, LINGKUNGAN KERJA , PENGHARGAAN DAN PEMBERIAN SOFT SKILL PADA PT. MAKMUR KARYA PERSADA MAKASSAR - Erfan, Muhammad; Iskandar, Muh. Reski (Universitas Ichsan Sidenreng Rappang, 2025)
This study aims to determine and analyze employee work ability based on factors of Work Experience, Work Environment, Awards and Soft Skills and which variables are dominant in influencing PT Makmur Karya Persada Makassar. The type of research used is quantitative analysis. In this study, the analysis method used is regression analysis, in this case the regression used is multiple regression analysis using SPSS software version 26. Based on the results of the study, it shows that the Soft Skill, Awards, work environment, and work experience variables together have a significant influence on employee performance and have a very strong influence on employee performance. The Soft Skill variable partially has a dominant influence on employee performance at PT. Makmur Karya Persada Makassar This means that in order to achieve more effective employee performance based on the goals and expectations of the organization, employees must be given good training and education in order to improve their technical abilities and skills based on the main functions and duties of an employee.